2011
DOI: 10.3174/ajnr.a2497
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Somatotopy of the Spinothalamic Pathway at the Ventroposterolateral Nucleus of the Thalamus in the Human Brain

Abstract: BACKGROUND AND PURPOSE:The STP has been regarded as the most plausible neural tract responsible for pathogenesis of central poststroke pain. The VPL nucleus has been a target for neurosurgical procedures for control of central poststroke pain. However, to our knowledge, no DTI studies have been conducted to investigate the somatotopic location of the STP at the VPL nucleus of the thalamus. In the current study, we attempted to investigate this location in the human brain by using a probabilistic tractography t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…It encompasses the postcentral gyrus on both the left and right sides of the brain and has a well described somatotopic map, with the leg represented medially in the paracentral lobule and the hand and face more laterally towards the parietal operculum. A few fMRI studies have examined somatotopy of the somatosensory pathway in healthy subjects (DaSilva et al, ; Hong, Kwon, & Jang, ) and in pain patients (Maleki et al, ; Shokouhi et al, ) and their connectivity (Yamada et al, ). Both these regions show plasticity in pain (Hubbard et al, ; Kim, Kim, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It encompasses the postcentral gyrus on both the left and right sides of the brain and has a well described somatotopic map, with the leg represented medially in the paracentral lobule and the hand and face more laterally towards the parietal operculum. A few fMRI studies have examined somatotopy of the somatosensory pathway in healthy subjects (DaSilva et al, ; Hong, Kwon, & Jang, ) and in pain patients (Maleki et al, ; Shokouhi et al, ) and their connectivity (Yamada et al, ). Both these regions show plasticity in pain (Hubbard et al, ; Kim, Kim, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One striking aspect of the organization of this system is that the spatial relationship 75 among the receptors in the body is conserved along this journey between the body 76 and the brain (Hong et al, 2011;Yamada et al, 2007), the consequence of which is 77 the presence of an orderly, somatotopically organized representation of the body in 78 primary somatosensory cortex -i.e., the sensory homunculus (Schott, 1993). 79…”
Section: Introduction 47mentioning
confidence: 99%
“…The recent development of diffusion tensor tractography (DTT), images of which are reconstructed from diffusion tensor imaging (DTI) data, allows three-dimensional visualization and estimation of the STT [3]. Many studies using DTT have reported that injury of the STT is related to the pathophysiology of central pain in mild TBI [2][3][4][5][6][7][8][9]. Most of these studies have reported on central pain of the arm and leg.…”
Section: Introductionmentioning
confidence: 99%